AADL architecture model construction based on FACE mode - LYU Guangzhe; YU Chunhai; KANG Kai; MA Chunyan; LIN Wei (Xibei Gongye Daxue Xuebao)
In the development of time-sensitive, mission-critical aerospace software systems, the modeling technology that combines the FACE(future airborne capability environment) open architecture model with the AADL(architecture analysis & design language) architectural model is gradually becoming a research hot spot. This paper proposes an automatic construction method for AADL models based on the FACE model. Firstly, the formal definition of the syntactic structure of the FACE model is given using context-independent grammar. Secondly, the 26 kinds of mapping rules from FACE model elements to AADL model elements are designed, and the rationality of the mapping rules is proved by the graph homomorphism theory. Then, the StringTemplate template is designed based on the mapping rules, and the template engine algorithm for generating AADL model is given. Finally, a total of 12 kinds of FACE models elements in four aspects are taken as experimental objects, 241 FACE model instances are designed as test cases, and the generated AADL models are verified in the OSATE tool. The method in this paper has been applied in the aviation field. The results can avoid repeated modeling work in the preliminary design stage and the detailed design stage.